TDP-43 Proteinopathy and Motor Neuron Disease in Chronic Traumatic Encephalopathy - McKee, Ann C.; Gavett, Brandon E.; Stern, Robert A.; Nowinski, Christopher J.; Cantu, Robert C.; Kowall, Neil W.; Perl, Daniel P.; Hedley-Whyte, E. Tessa; Price, Bruce; Sullivan, Chris; Morin, Peter; Lee, Hyo-Soon; et al. (Journal of neuropathology and experimental neurology, 2010)
Epidemiological evidence suggests that the incidence of amyotrophic lateral sclerosis is increased in association with head injury. Repetitive head injury is also associated with the development of chronic traumatic encephalopathy (CTE), a tauopathy characterized by neurofibrillary tangles throughout the brain in the relative absence of β-amyloid deposits. We examined 12 cases of CTE and, in 10, found a widespread TAR DNA-binding protein of approximately 43kd (TDP-43) proteinopathy affecting the frontal and temporal cortices, medial temporal lobe, basal ganglia, diencephalon, and brainstem. Three athletes with CTE also developed a progressive motor neuron disease with profound weakness, atrophy, spasticity, and fasciculations several years before death. In these 3 cases, there were abundant TDP-43-positive inclusions and neurites in the spinal cord in addition to tau neurofibrillary changes, motor neuron loss, and corticospinal tract degeneration. The TDP-43 proteinopathy associated with CTE is similar to that found in frontotemporal lobar degeneration with TDP-43 inclusions, in that widespread regions of the brain are affected. Akin to frontotemporal lobar degeneration with TDP-43 inclusions, in some individuals with CTE, the TDP-43 proteinopathy extends to involve the spinal cord and is associated with motor neuron disease. This is the first pathological evidence that repetitive head trauma experienced in collision sports might be associated with the development of a motor neuron disease.